Cellular Modulation of Polymeric Device Surfaces: Promise of Adult Stem Cells for Neuro-Prosthetics - Richter, Anja; Kruse, Charli; Moser, Andreas; Hofmann, Ulrich G.; Danner, Sandra (Frontiers in Neuroscience, 2011)
Minimizing the foreign body response is seen as one critical research strategy for implants especially when designed for immune-privileged organs like the brain. The context of this work is to improve deep brain stimulating devices used in a consistently growing spectrum of psychomotor and psychiatric diseases mainly in form of stiff electrodes. Based on the compliance match hypothesis of biocompatibility we present another step forward using flexible implant materials covered with brain cell-mimicking layers. We covered two types of flexible polyimide films with glandular stem cells derived from pancreatic acini. Using real time-PCR and fluorescent immunocytochemistry we analyzed markers representing various cell types of all three germ layers and stemness. The results demonstrate an unchanged differentiation potential of the polyimide fixated cells as measured by mRNA and protein level. Additionally we developed a fibrinous hydrogel coating to protect them against shear forces upon eventual implantation. By repeating previous analysis and additional metabolism tests for all stages we corroborate the validity of this improvement. Consequently we assume that a stem cell-containing cover may provide a native, fully and actively integrating brain-mimicking interface to the neuropil.